MODELLING OF THE ROUTE NETWORK FOR PERISHABLE CARGO DELIVERY IN THE REGIONAL TRAFFIC ON THE BASIS OF PETRI NETS: Array - Potaman, N.; Shulika О.; Оrda O. (Municipal economy of cities. Series: «Economy science», 2021)
The article is devoted to the features of the organization and technology of delivery of perishable goods in small batches by road in regional traffic. It has been established that when planning this type of cargo delivery, it becomes necessary to determine such routes bypassing specified points, at which the time of delivery of perishable goods to points of sale will be minimal. Thus, as a criterion that determines the rationality of building a route network for the delivery of perishable goods in regional traffic, has been defined the time of cargo’s delivery in small batches in regional traffic. The route network for the delivery of perishable goods with a minimum delivery time is considered rational. To analyze the execution time of each delivery phase and take into account the time and quantitative parameters that affect the delivery process, the study built a model which is based on the theory of Petri nets. The parameters of the model were established on the basis of the reporting data of the private enterprise "Samoilenko A.I.". The model took into account time parameters and quantitative factors affecting the process of delivery of perishable goods in regional traffic. An experiment was carried out using the developed model. The obtained value of the integral error of the data discrepancy throughout the system allows us to assume that the constructed model adequately reproduces the process of delivery of perishable goods in small batches by road in regional traffic. Taking into account the results of delivery process’ modeling, using the method of a short connecting network, a rational route network was built in the study, which consists of six routes. The effect was determined as a time difference for the delivery system along the network of rational route network and along the existing network, which amounted to 131 minutes.